Reliability evaluation of Si-dies due to assembly issues. (September 2016) - Naumann, F.; Gottschalk, V.; Burchard, B.; Altmann, F.
Abstract: Silicon based semiconductor devices are stressed during fabrication, handling and packaging with significant thermal and mechanical loadings. In worst cases, these induced loadings can cause initial chip damage leading to electrical failure or fracture of the Si-die during further process steps or application. In order to evaluate the risk of pre-damage during assembly, a case study of potential failure modes taking pick-and-place processes into account was performed. Therefore, pre-damaged samples using a misaligned pick-and-place setup were generated. Afterwards, methods of microstructural crack analyses and mechanical strength testing were applied to evaluate the damage impact of the generated needle imprint. In addition, finite element analyses in combination with fracture mechanical approaches were combined to evaluate the failure probability of Si-dies during the following assembly or thermal cycling steps. As a result of this study, critical process steps during chip assembly can be identified and critical tolerance limits of the process can be evaluated to achieve an acceptable reliability level. Consequently, the risk of failure caused by handling or assembly issues can be estimated and appropriate steps for quality assurance procedures can be defined. Highlights: The influence of assembly steps to the reliability of a packaged Si-Chip was investigated. Fracture mechanical approaches in combination with micro-structural investigations, FEA modelling and strength testing were used. The risk of die-cracking after packaging is estimated.